Spectral characteristics of coupled plasmonic modes in aggregates of plasma columns - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2012)
Theoretical study of the eigenfrequencies of coupled plasmons in cylindrical plasma columns is presented. Plasmonic modes of linear chain of coupled plasma cylinders and cluster of square configuration is investigated. Mechanism of the plasmonic mode coupling that can be considered as bonding and antibonding combinations of isolated cylinder plasmons is studied. Accurate analysis of the spectrum of different plasmon resonances and their quality factors is presented.
Keywords: surface plasmons; plasmon resonances; eigenfrequency; linear chain